Über den Bau der Antennen von Formica pratensis Retzius, 1783, unter besonderer Berücksichtigung der Sensillen. - Kürschner, Isa (Contributions to Entomology = Beiträge zur Entomologie, 1969)
The present paper described structural elements of the antennae of Formica pratensis Retzius, 1783, especially their sensilla, and discusses them as far as that is possible. The following sensilla can be identified: Sensilla trichodea, Sensilla basiconica, Sensilla placodea, Sensilla coeloconia, Sensilla ampullacea. A sensillum not previously described which is always on the last segment of the funiculus could not be fitted into the current nomenclature. Possibly additional neurosecretory processes play a part in the nerval connection between the sensilla and the nervus antennalis, as it is indicated by the presumable detection of neurosecretion. Relations between a basophilic, possibly glandular cell complex and big cells are established. The nervus antennalis is enclosed almost to the tip of the funiculus by a continuation of the dorsal vessel and a ramifying trachea.